Hereditary hemochromatosis (Clinical case) - Sousa, Bruno (2022)
A sixty-eight-year-old retired man was sent for Nutrition Consultation by his family doctor due to hereditary hemochromatosis (homozygosity H63D) and other pathologies that require nutritional therapy. He was also sent to a Transfusion Medicine and Rheumatology Consultation.